1978
DOI: 10.1128/jb.134.1.200-207.1978
|View full text |Cite
|
Sign up to set email alerts
|

L-Asparagine auxotrophs of Saccharomyces cerevisiae: genetic and phenotypic characterization

Abstract: L-Asparagine auxotrophy in Saccharomyces cerevisiae is the result of mutation in each of two unlinked cistrons, ASN1 and ASN2. Mutation in only one of these cistrons yields growth indistinguishable from that of wild-type cells under a variety of nutritional stresses. Relatively high concentrations of L-asparagine are required to permit maximal growth of the auxotrophs, and the amino acid requirement cannot be satisfied by a variety of other amino acids that serve as nitrogen sources for cell growth. Although r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
1
7
1
Order By: Relevance
“…This double disruption leads to total auxotrophy for asparagine (data not shown). This result confirms that a double mutant is required in yeast to obtain asparagine auxotrophy (Jones, 1978;Ramos and Wiame, 1979).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This double disruption leads to total auxotrophy for asparagine (data not shown). This result confirms that a double mutant is required in yeast to obtain asparagine auxotrophy (Jones, 1978;Ramos and Wiame, 1979).…”
Section: Resultssupporting
confidence: 81%
“…Isogenic wild-type and disrupted strains were tested for growth in the absence of asparagine, and no growth defect could be detected in the asn1 or asn2 mutant strains (data not shown). These results are in agreement with those from Jones (1978) who could not find any growth defect associated with the asn1 or asn2 single mutants. In another report, Ramos and Wiame (1979) observed that an asnA mutation leads to a partial auxotrophy while asnB mutants were totally prototrophic.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations